Pengaruh Penyuluhan Kesehatan MP ASI terhadap Peningkatan Pengetahuan Ibu Balita di Dusun Gelangan Desa Tlogomulyo - Siswati; Vistra Veftisia (Universitas Ngudi Waluyo, 2024)
Nutrition is an important component in life. Fulfillment of nutrition does not only focus on the type and amount but must pay attention to the method, quantity, age of babies and toddlers. For babies aged 0-6 months, nutrition can be met with breast milk alone. However, after the age of 6 months, additional nutrition is needed in the form of complementary foods for breast milk (MP ASI), which are foods/drinks with balanced nutrition for toddlers aged 6-24 months. Providing MP-ASI is a gradual process of transitioning intake from breast milk to semi-solid family food in terms of type, quantity, frequency, texture and consistency according to the needs of toddlers. Providing correct MP-ASI affects the child's growth and development process and his intelligence. However, inappropriate MP-ASI will cause problems in children's nutritional status, one of which is malnutrition. A phenomenon that is still often encountered is the mother's lack of understanding in providing appropriate complementary foods. The problem of lack of maternal knowledge affects the growth and development of toddlers. Based on the problems that arise, community service activities are needed to overcome these problems. This activity began with a pre-test related to MP ASI which was attended by 10 mothers of stunted toddlers who then provided material about MP ASI and continued with an evaluation in the form of a post test. From this activity, the result was an increase in the knowledge of mothers of toddlers about MP ASI. Abstrak Nutrisi merupakan salah satu komponen penting dalam kehidupan. Pemenuhan nutrisi tidak hanya berfokus pada jenis dan jumlahnya saja tetapi harus memperhatikan cara, kuantitas, umur bayi dan balita. Bagi bayi usia 0-6 bulan, nutrisi dapat dipenuhi dengan ASI saja. Namun, setelah usia 6 bulan dibutuhkan gizi tambahan berupa Makanan Pendamping ASI (MP ASI) yang merupakan makanan/ minuman dengan zat gizi seimbang bagi balita usia 6-24 bulan. Pemberian MP-ASI merupakan proses transisi asupan dari ASI menuju makanan keluarga semi padat secara bertahap baik jenis, jumlah, frekuensi, tekstur dan konsistensinya sesuai kebutuhan balita. Pemberian MP-ASI yang benar, berpengaruh pada proses tumbuh kembang anak dan kecerdasannya. Namun, MP-ASI yang tidak sesuai akan menimbulkan masalah dalam status gizi anak salah satunya masalah gizi kurang/ gizi buruk. Fenomena yang masih banyak ditemui adalah kurangnya pemahaman ibu dalam pemberian MP ASI yang tepat. Masalah kurangnya pengetahuan ibu ini mempengaruhi tumbuh kembang balita. Berdasarkan masalah yang muncul, maka diperlukan kegiatan pengabdian masyarakat untuk mengatasi hal tersebut. Kegiatan ini diawali dengan pre test berkaitan dengan MP ASI yang diikuti oleh 10 ibu balita stunted kemudian memberikan materi tentang MP ASI dan dilanjutkan dengan evaluasi berupa post test. Dari kegiatan tersebut didapatkan hasil adanya peningkatan pengetahuan ibu balita tentang MP ASI.